Gut microbiome differences and disease risk in colorectal cancer relatives and healthy individuals - Wang, Huifen; Zhu, Weiwei; Lei, Jun; Liu, Zhibo; Cai, Yudie; Wang, Shuaifeng; Li, Ang (Frontiers in Cellular and Infection Microbiology, 2025)
Given the heightened focus on high-risk populations, this study aimed to provide insights into early susceptibility and preventive strategies for colorectal cancer (CRC) by focusing on high-risk populations. In this research, fecal samples from 1,647 individuals across three discovery cohorts and nine external validation cohorts were sequenced using whole-genome metagenomic sequencing. A prediction model based on random forest was constructed using the nine external cohorts and independently validated with the three discovery cohorts. A disease probability (POD) model based on microbial biomarkers was developed to assess CRC risk. We found that the gut microbiome composition of CRC relatives differed from that of controls, with enrichment of species such as Fusobacterium and Bacteroides and a reduction in beneficial genera like Coprococcus and Roseburia. Additionally, dietary red meat intake emerged as a risk factor. The POD model indicated an elevated risk of CRC in unaffected relatives. The findings suggest that the POD for CRC may be increased in unaffected relatives or individuals living in shared environments, although this difference did not reach statistical significance. Our study introduces a novel framework for assessing the risk of colorectal cancer in ostensibly healthy individuals.